Comparative analisys of neuron densities in cortical areas of different dogs breed - Esteves, Alessandra (2008)
They were studied and compared the neuronal densities of the cerebral cortex of three dogs races, with constitutional types, characteristic and different functional aptitudes amongst themselves. Of the brain they were solitary fragments of the different areas of the cerebral cortex, corresponding to the system limbic, visual, hearing, motor, palate, sense of smell and to the area somestesic. Through counting appearance-manual, comparative data were looked for, among areas cerebral versus race associating types constitutional versus aptitude. The factors races, functional areas and cerebral hemispheres can be dependent variables amongst themselves, because they were found differences significant estimation in values corresponding to the average of density of neurons of the areas studied in the different races, as well as he/she enters the cerebral hemispheres. The results allow to end that the quantitative distribution of neurons in the different areas studied cortical display significant differences that establish correlations with the aptitudes functional.